Single Meaning Dan Multiple Meaning dalam Interpretasi Injil Yohanes 4:21-24 dan Implikasinya Bagi Gereja Masa Kini - Kristien Oktavia; Robinson Rimun (Jurnal Teologi Praktika, 2021)
The interpretation of the meaning of the Gospel of John 4: 21-24 is not fully understood by some theologians and church circles today, which only includes a single meaning in a category, namely the category of ways or actions, the category of expression or power of the Spirit, the category of places of worship (practice), and the category of places of worship (practice). Right on target (pattern) in worship of God, so that this meaning does not cover the entire meaning and purpose of the Gospel of John (John 20:31), which should be analyzed as a whole in the Gospel of John. 4: 1-42, according to the interpretation of the Bible which clarifies or clarifies the meaning of language by means of precise and clear analysis. with the meaning contained is it only limited to single meaning or multiple meaning? namely a single meaning that is expanded in terms of language, so it is often understood as a double meaning. The most important thing as a complete understanding is that the Bible is single meaning or multiple meaning, which means one interpretation, but many applications  Therefore the author uses a qualitative research design, which is not experimental oriented with the type of biblical theological research, on the basis of the use of descriptive analysis methods from various data sources. The method used is biblical research (exegesis), namely the principles of hermeneutics. With the aim of this research is to know the various interpretations and interpretations of the Gospel of John 4: 21-24, so as to know the implications for the church today. So that it can be revealed that the various interpretations of theologians have not completely covered the meaning contained in the Gospel of John 4: 1-42, because they only highlight one of the limited meanings of verses 23-24. Where as a whole speaks of a single commandment in carrying out the mission of Jesus, with eight meanings contained in the entire historical journey of Jesus. The meaning of this single commandment has implications for the church today in broad understanding of the Gospel of John 4: 1-42.AbstrakInterpretasi pada makna Injil Yohanes 4:21-24 dipahami kurang menyeluruh oleh beberapa teolog dan kalangan gereja masa kini, yang hanya mencakup sebatas kategori yaitu kategori cara atau tindakan, kategori ekspresi atau kuasa Roh, kategori tempat ibadah (praktik), dan kategori tepat sasaran (pola) dalam penyembahan kepada Tuhan, sehingga makna ini tidak mencakup seluruh makna dan tujuan Injil Yohanes (Yoh. 20:31), yang seharusnya di analisa secara keseluruhan pada Injil Yoh. 4:1-42, sesuai dengan interpretasi Injil yang memperjelas atau menjernihkan makna bahasa dengan sarana analisis yang tepat dan jelas. Dengan makna yang terkandung apakah hanya sebatas single meaning atau multiple meaning yang artinya makna tunggal yang diperluas dalam segi kebahasaan, sehingga sering dipahami sebagai makna ganda. Hal terpenting sebagai pemahaman secara utuh, bahwa Alkitab bersifat single meaning atau multiple meaning, yang berarti satu tafsiran, namun banyak pengertian Oleh karena itu penulis menggunakan rancangan penelitian kualitatif, yang berorientasi bukan eksperimental dengan jenis riset teologi biblika, dengan dasar penggunaan metode deskriptif analisis dari berbagai sumber data. Metode yang dipakai adalah penyelidikan Alkitabiah (eksegesis) yaitu dengan prinsip-prinsip hermeneutika. Dengan tujuan penelitian ini adalah mengetahui ragam tafsiran dan interpretasi Injil Yohanes 4 : 21-24, sehingga dapat mengetahui implikasi bagi gereja masa kini. Sehingga dapat mengungkapkan bahwa ragam tafsiran para teolog belum mencakup secara menyeluruh tentang makna yang terkandung dalam Injil Yohanes 4:1-42, karena hanya menyoroti salah satu makna sebatas ayat 23-24. Dimana secara keseluruhan berbicara tentang perintah tunggal dalam melaksanakan misi Yesus, dengan delapan makna yang terkandung di dalam seluruh historis perjalanan Yesus. Makna perintah tunggal ini dapat menjadi implikasi bagi gereja masa kini untuk dapat mengetahui makna secara luas tentang Injil Yohanes 4: 1-42.